Chronic exposure to aflatoxigenic fungi related to liver damage in pelt chinchillas (Chinchilla lanigera) - Landa, M F; González-Pereyra, M L; Pena, G; Bagnis, G; Cavaglieri, L R; Da Rocha-Rosas, C A; Dalcero, A M (Revista Bio Ciencias, 2013)
Chinchilla pelt is a rare and expensive fur. Therefore, breeding these animals is a profitable activity. Confirmed acute cases of aflatoxinintoxication have been reported in Argentinean farms. The aims of this study were i) to evaluate mycobiota and AFB1-producing species in chinchilla feeds ii) to investigate their natural AFB1 contamination and iii) to analyze histopathological lesions in chinchilla livers. Feed samples (A: fur chinchillas, B: mother chinchillas, C: lucerne cubes) were collected from a factory anda farm. Livers of sacrificed chinchilla from the farm were macroscopically and microscopically examined. Total fungal counts of feed C exceeded 1x104 CFU g-1. Aspergillus, Fusarium and Penicillium were the prevalent genera, while A. flavus, A. fumigatus, F. verticillioides and F.proliferatum were the prevalent species. 50 % of A. flavus strains from factory samples and 69.7 % from farm samples produced 2.78 to 8.64 μg g-1 and 0.66 to 58.8 μg g-1 AFB1, respectively. Aflatoxin B1 was detected only in feeds from the farm, finding the highest incidence in feed C. Toxin levels varied between 1.90 and 97.34μg kg-1 AFB1. Mean levels in feed A and C exceeded 20 μg kg-1. Macroscopic examination of livers revealed normal appearance, size and color. However, histopathological examination indicated 63.3 % showed slight to moderate lipidde generation with diffuse cytoplasm vacuolation,9 % intense lipid cytoplasm vacuolation and 27.3 % hydropic degeneration and nuclear vacuolation in hepatocytes. A periodic monitoring of aflatoxins in feeds and their ingredients can prevent acute outbreaks and economic losses caused by chronic exposure.